Study Komparatif Tentang Hukum Jual Beli Sistem ‘Urbun Atau Down Payment Menurut Madzhab Syafi’i dan Madzhab Hambali - Albadii, Loudri Fitria; Syafi'i, Ahmad; Ayu, Diyan Putri (Social Science Academic, 2023)
Bay 'urbun, otherwise known as buying and selling with an advance payment system. In the Al-Qur'an and Hadith, there is not much explanation regarding the terms of buying and selling with an 'urbun' or down payment system. The Syafi'i school prohibits buying and selling with advance payments, while the Hanbali school allows this system. The purpose of discussing this research is to find out the opinions of the two schools of thought regarding buying and selling of the 'urbun or down payment system and also the istinbath method used in. In this study using the research method library research, which comes from books, scriptures or pure essays. The aim is to provide information that can be researched about individuals, conditions, or other symptoms. The results of the discussion conclude that first, Imam Syafi'i's opinion absolutely does not allow buying and selling using the 'urbun system', besides that it also includes buying and selling that is fasid (damaged) and consumes rights in vain. Second, according to Imam Hanbali, the sale and purchase of the urbun system is permissible because both parties have agreed. Imam Shafi'i uses the hadith of Amr Ibn Syu'aib as the method of istinbath, while the Hambali School da'if it, they prefer hadiths originating from the narrations of Nafi' Ibn Harith and Umar Ibn Khattab as the legal basis.